2022
DOI: 10.7759/cureus.28763
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Direct Oral Anticoagulants and Warfarin in the Prevention of Stroke in Patients With Valvular Heart Disease: A Meta-Analysis

Abstract: Warfarin is the standard of care, and direct oral anticoagulants (DOACs) are a group of newer drugs to prevent stroke in patients with valvular heart disease. The aim of this meta-analysis is to compare the efficacy and safety of DOACs and warfarin in the prevention of stroke in patients with valvular heart disease (VHD). The current meta-analysis was conducted using the standards developed by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendation. The databases from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…To our knowledge, this marks the inaugural systematic review and network meta-analysis endeavoring to amalgamate the available advantages and drawbacks of newer oral anticoagulants for averting stroke and major bleeding occurrences in patients grappling with valvular heart disease. A recent meta-analysis by Batool et al [ 10 ], encompassing five randomized controlled trials (RCTs), concluded that DOACs exhibit greater efficacy than warfarin in preventing stroke and major bleeding events. Nonetheless, our current meta-analysis encompasses recently published RCTs as well as observational studies.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this marks the inaugural systematic review and network meta-analysis endeavoring to amalgamate the available advantages and drawbacks of newer oral anticoagulants for averting stroke and major bleeding occurrences in patients grappling with valvular heart disease. A recent meta-analysis by Batool et al [ 10 ], encompassing five randomized controlled trials (RCTs), concluded that DOACs exhibit greater efficacy than warfarin in preventing stroke and major bleeding events. Nonetheless, our current meta-analysis encompasses recently published RCTs as well as observational studies.…”
Section: Reviewmentioning
confidence: 99%
“…In patients with non-valvular AF, the non-inferiority of direct oral anticoagulants (DOACs) compared to warfarin has already been established [ 7 , 8 ]; hence, DOACs are widely adopted in routine clinical practice due to their avoidance of routine anticoagulation monitoring or dose adjustment [ 9 ]. DOACs have also proven effective as an alternative to warfarin in AF patients with valvular heart disease [ 10 ]. Current guidelines advocate for DOACs as the preferred initial therapy in AF patients with a bioprosthetic valve alongside warfarin [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…And, the risk of bleeding and all-cause mortality associated with warfarin is significantly higher than with other nonvitamin K-dependent direct oral anticoagulants (DOACs). 4 6 …”
Section: Introductionmentioning
confidence: 99%
“…Direct oral anticoagulants (DOACs) offer an alternative option for individuals with atrial fibrillation and have increasingly supplanted VKAs in clinical practice. For the majority of adults with atrial fibrillation, DOACs provide a significant net clinical benefit in preventing major thromboembolic events [ 8 , 9 ]. They are favored for their broader therapeutic window and ease of use, owing to fixed oral dosing and reduced need for regular laboratory monitoring or dose adjustments compared to VKAs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%